Peran Kiprah Kiai Ahmad Siraj : Ulama Pendiri Nahdlatul ‘Ulama dan Pejuang Kemerdekaan di Surakarta (1926-1948) (DIAKRONIK: Jurnal Pemikiran dan Penelitian Sejarah, 2025)
This research explain the work of Kiai Ahmad Siraj as a founding cleric of Nahdlatul ‘Ulama and freedom fighter in Surakarta in the period 1926-1948. Kiai Ahmad Siraj was born in Semarang in 1878 with a family background of kiai. He studied with Kiai Imam Bahri Mangunsari, Kiai Dimyati At-Tirmidzi and Kiai Sholeh Darat, and was also a follower of Tarekat Qadiriyah wa Naqsyabandiyah. Kiai Ahmad Siraj began his work as a scholar who became one of the pioneers of the establishment of Nahdlatul ‘Ulama Surakarta. During the pioneering period, Kiai Ahmad Siraj was also active in broadcasting and developing Nahdlatul ‘Ulama Surakarta. In addition, Kiai Ahmad Siraj also took part with Barisan Kiai to defend independence in Surakarta in 1945-1948. He became an important figure for Laskar Hizbullah Surakarta in providing prayers, motivation, direction and physiological and psychological training